Naturally Biased Associations Between Music and Poetry. (February 2017) - Albertazzi, Liliana; Canal, Luisa; Micciolo, Rocco; Ferrari, Fulvio; Sitta, Sebastiano; Hachen, Iacopo
The study analyzes the existence of naturally biased associations in the general population between a series of musical selections and a series of quatrains. Differently from other studies in the field, the association is tested between complex stimuli involving literary texts, which increases the load of the semantic factors. The stimuli were eight quatrains taken from the same poem and eight musical clips taken from a classical musical version of the poem. The experiment was conducted in two phases. First, the participants were asked to rate 10 couples of opposite adjectives on a continuous bipolar scale when reading a quatrain or when listening to a musical clip; then they were asked to associate a given clip directly with the quatrains in decreasing order. The results showed the existence of significant associations between the semantics of the quatrains and the musical selections. They also confirmed the correspondences experienced by the composer when writing the musical version of the poem. Connotative dimensions such as rough or smooth, distressing or serene, turbid or clear, and gloomy or bright, characterizing both the semantic and the auditory stimuli, may have played a role in the associations. The results also shed light on the accomplishment of the two diverse methodologies adopted in the two different phases of the test. Finally, the role of specific musical components and their combinations is likely to have played an important role in the associations, an aspect that shall be addressed in further studies.